A guide to chalcogen-nitrogen chemistry - Chivers, T. (Tristram), 1940- (World Scientific, 2005)
"A Guide to Chalcogen-Nitrogen Chemistry examines the role of chalcogen-nitrogen compounds in areas ranging from solid-state inorganic chemistry to biochemistry. The discussion covers fundamental questions concerning the bonding in electron-rich systems, as well as potential practical applications of polymers and materials with novel magnetic or electrical properties. This book is the only account of this important topic to appear in the last twenty-five years, and coupled with its extensive literature coverage of very recent developments, this comprehensive guide is essential for anyone working in the field. The treatment is unique in providing a comparison of sulfur, selenium and tellurium systems, with an approach intended to emphasize general concepts that will be helpful to the non-specialist. Each chapter is designed to be self-contained, and there are extensive cross-references between chapters."--Jacket